Process-Outcome Associations in an Interdisciplinary Treatment for Chronic Pain and Comorbid Mental Disorders Based on Acceptance and Commitment Therapy. Issue 11 (23rd March 2021) - Ohse, Ludwig; Burian, Ronald; Hahn, Eric; Burian, Hanna; Ta, Thi Minh Tam; Diefenbacher, Albert; Böge, Kerem
Abstract: Objective: Numerous studies support the effectiveness of acceptance and commitment therapy (ACT) for chronic pain, yet little research has been conducted about its underlying mechanisms of change, especially regarding patients with comorbid mental disorders. The present investigation addressed this issue by examining associations of processes targeted by ACT (pain acceptance, mindfulness, psychological flexibility) and clinical outcomes (pain intensity, somatic symptoms, physical health, mental health, depression, general anxiety). Subjects: Participants were 109 patients who attended an ACT-based interdisciplinary treatment program for chronic pain and comorbid mental disorders in a routine care psychiatric day hospital. Methods: Pre- to posttreatment differences in processes and outcomes were examined with Wilcoxon signed-rank tests and effect size r . Associations between changes in processes and changes in outcomes were analyzed with correlation and multiple regression analyses. Results: Pre- to posttreatment effect sizes were mostly moderate to large ( r between 0.21 and 0.62). Associations between changes in processes and changes in outcomes were moderate to large for both, bivariate correlations ( r between 0.30 and 0.54) and shared variances accounting for all three processes combined ( R 2 between 0.21 and 0.29). Conclusion: The present investigation suggests that changes in pain acceptance, mindfulness, and psychological flexibility are meaningfully associated with changes in clinical outcomes. It provides evidence on particular process-outcome associations that had not been investigated in this way before. The focus on comorbid mental disorders informs clinicians about a population of chronic pain patients who often have a severe course of illness and have seldom been studied.